Bruceine H Mediates EGFR-TKI Drug Persistence in NSCLC by Notch3-Dependent β-Catenin Activating FOXO3a Signaling - Wu, Jiahui; He, Xiao; Xiong, Ziwei; Shi, Lingyu; Chen, Daofeng; Feng, Yulin; Wen, Quan (Frontiers in Oncology, 2022)
In non-small cell lung cancer treatment, tyrosine kinase inhibitors (TKIs) that target the epidermal growth factor receptor (EGFR) gene serve as a critical pillar, but resistance is universal. Identifying the potential key factors of drug resistance to EGFR-TKI inhibitors is essential for the treatment of patients with EGFR mutant lung cancer. Our research here shows that Bruceine H, a Notch3 inhibitor, suppressed proliferation, migration, and invasion of lung cancer cells, inhibited the growth of human NSCLC cell xenografts, and enhanced the therapeutic effects of Gefitinib in the PC-9/GR xenograft models. In order to analyze the potential targets of the combination of Notch3 and EGFR-TKI inhibitors on resistance to EGFR, we performed the difference in gene expression between non-small cell lung cancer (NSCLC) tissues and EGFR-driven-Gefitinib resistant tumoral groups, then identify through the WGCNA key genes that may provide therapeutic targets for TKI-resistant lung cancer xenograft models. We demonstrate that the combination of EGFR-TKI and a Notch3 inhibitor inhibits the expression of β-catenin, enhances the level of FOXO3a, improves recurrence free survival, and overall survival in xenograft models. These results support a combination of Gefitinib therapy and Notch3 inhibitors may provide a promising alternative strategy for treating acquired EGFR-TKI resistance in patients with NSCLC.